EVALUASI SISTEM INFORMASI MYNURZ MENGGUNAKAN FRAMEWORK COBIT 5 DOMAIN EDM DSS DAN MEA PADA PT KRONUS INDONESIA - Panji Rusdiyanto (2020)
With the presence of the MyNurz application created by the Indonesian organization Kronus, which is offered to encourage clients in requesting clinical faculty. Complete the assessment on the MyNurz application framework that is relied upon to be performed Performance assessment of the MyNurz application. Along these lines, this examination was directed to evaluate the degree of ability right now got utilizing COBIT 5 work. In this investigation, scientists were solicited to direct an evaluation from ability levels all the while. Guaranteeing the courses of action and enhancements appeared by administration plans (EDM01) Resources (EDM04) Manage Service and Incident Assistance (DSS02), Manage Problems (DSS03), Manage Security Services (DSS05), Monitor, Evaluate and Support Performance and Compliance (MEA01), Monitor, Evaluate and utilize the Internal Control System (MEA02). Subsequent to computing the ability level, it is realized that the chose procedure is acquired at level 3 (three). In particular the procedure that has been made can be applied by utilizing a procedure that can accomplish the consequences of the procedure and for the objective to be accomplished at level 4 (Four).